Open access policy guidelines by the MedOANet project: Facilitating open access policy development in Mediterranean Europe - Nafpliotis, Alexandros; Tsoukala, Victoria; Kalaitzi, Vasso (Septentrio Conference Series, 2014)
See video of the presentation. Toward the end of the two-year EC-funded project Mediterranean Open Access Network (MedOANet; www.medoanet.eu) this presentation offers a summary of its activities and specifically focuses on the culminating outcome of the project, the guidelines for policy development, directed to research performing organizations and research funders in six countries: Greece, Italy, Turkey, France, Spain and Portugal. The guidelines are to be released in English in all six languages of the project partners in September 2013. Purpose of the project is to support and strengthen coordinated policy development among funders and research organizations of the six countries (www.medoanet.eu). For two years the project has enabled open access policy developments through activities at the national level, such as the development of task forces and national conferences that brought together major stakeholders and policymakers, as well as regional developments through a European workshop in Braga, Portugal in early spring 2013. The project has, further, mapped the open access policy situation in the six countries, the results of which are to be published in the early fall 2013. Three surveys carried in six countries among research funders, research performing organizations and publishers demonstrate that the momentum towards open access requires specific policy actions to actually render publicly funded research openly accessible to all. The guidelines under preparation by the project discuss the key principles and processes to be followed by funding and research performing organizations in establishing open access policies, highlighting the most important steps necessary in defining and implementing effective policies. Significantly, they also offer model policies for research funders and research performing organizations. The model policies have been elaborated on the basis of current models and recent relevant developments, and emphasize mandatory green open access. The proposed presentation will discuss their components in detail. The effect of the guidelines and model policies are eagerly awaited and already expected to be significant as a number of institutions in Greece and other countries are discussing adopting them together.